The impact of nickel mining on vegetation cover in a small island: a case study in Manuran Island, Raja Ampat, Indonesia - Adidharma, Mohammad Afdhal; Mu’min Z, Nurul; Santrio, Adam; Idris, Andi Azwar Anas; Fatmi, Anggun Rahmi Diah; Awaluddin, Awaluddin; Pindasari, Nanang; Ermawati, Elly; Padyawan, Andhy Rahmat; Sirniawan, Sirniawan (Brawijaya University, 2026)
The exploitation of small islands (area less than 2000 km²) for mining activities can negatively impact vegetation conditions, as observed on Manuran Island in West Papua Province. This study aimed to assess the environmental impact of mining on Manuran Island by analyzing spatial and temporal changes in vegetation indices using the Normalized Difference Vegetation Index (NDVI) method to classify land cover using Landsat 7 ETM satellite imagery and Landsat 8 OLI imagery. The NDVI classification grouped four land cover types: non-vegetation, open soil, sparse vegetation, and moderate vegetation. The analysis revealed a significant increase in non-vegetation land cover from 2002 to 2015, indicating a direct impact from mining activities. However, between 2015 and 2025, the area classified as non-vegetation tended to decrease gradually. Conversely, open soil and sparse vegetation experienced a notable decline from 2002 to 2015, followed by a minor decrease in the subsequent period. In contrast, moderate vegetation steadily increased from 2002 to 2025, suggesting a recovery process in the vegetation. To accelerate the environmental and vegetation recovery process, several revegetation strategies, including reclamation, selection of native and pioneer species, and soil improvement techniques, are recommended. The findings of this study suggest that the reduction in mining activity intensity on Manuran Island has contributed positively to ecosystem recovery and that direct interventions are needed to accelerate environmental recovery.